If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(3x-1)=3(2x+5)
We simplify the equation to the form, which is simple to understand
7(3x-1)=3(2x+5)
Reorder the terms in parentheses
+(+21x-7)=3*(2x+5)
Remove unnecessary parentheses
+21x-7=+3+*(+2x+5+)
Reorder the terms in parentheses
+21x-7=+(+6x+15)
Remove unnecessary parentheses
+21x-7=+6x+15
We move all terms containing x to the left and all other terms to the right.
+21x-6x=+15+7
We simplify left and right side of the equation.
+15x=+22
We divide both sides of the equation by 15 to get x.
x=1.4666666666667
| 4-5x=x-3 | | 7.65x+61.2=122.4 | | 0.15d+0.07(1000-d)=130 | | -2+2k+3=-3 | | 4x+28=2x | | 8-3x+7x=15-3x | | 0.125y+0.1(800-y)=85 | | X+1+3=4 | | 2.7(-16)+2.2=2.4(-16)-2.6 | | 3(1)+6= | | 0.05+0.09(3x)=32 | | 6.5y-3=5.5y+1 | | x+(.05x)=49.77 | | -v-2v=-9 | | 6.5y-3=5.5+1 | | 4(g+2)+3=19 | | 42x-7=9-4 | | 4(x+2)=21(x-3) | | 3-v=1 | | 1-3n-2n=-4 | | 1-v-3=0 | | 2.7x+2.2=2.4x-2.6 | | 1-v-3=I | | (3+v)(4v+1)=0 | | 10x+3=3+12x | | 20-6x=34 | | 1-z=7.2 | | 9x^2+11x+9=0 | | 2xsquared=6x | | -5x+9=-71 | | 6n=17+7 | | 3x-8+x=2(2x-4) |